1995
DOI: 10.1002/jmv.1890450305
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of genomic polymorphism among herpes simplex virus type 2 isolates from four areas of Japan and three other countries

Abstract: Genomic polymorphism of 307 epidemiologically unrelated strains of herpes simplex virus type 2 (HSV-2) from four areas of Japan and three other countries (Korea, Sweden and the U.S.A.) was analysed by using 16 variable markers selected from 97 restriction endonuclease (RE) sites with five REs. In addition to the 16 markers, 26 rare variable RE sites were found in 307 isolates. Five and four of 16 markers (RE sites) were found to differ in the frequency of isolates with the markers between isolates from Japan a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…Thus, the LAMP target and primer regions of HSV-1 are regarded as having adequately low degrees of variation. Compared to HSV-1, HSV-2 and VZV have little nucleotide diversity among strains (2,17,19). Our sequencing study indicated that the targeted regions of HSV-2 and VZV have no nucleotide sequence variation and are also adequate for the LAMP assay.…”
Section: Discussionmentioning
confidence: 77%
“…Thus, the LAMP target and primer regions of HSV-1 are regarded as having adequately low degrees of variation. Compared to HSV-1, HSV-2 and VZV have little nucleotide diversity among strains (2,17,19). Our sequencing study indicated that the targeted regions of HSV-2 and VZV have no nucleotide sequence variation and are also adequate for the LAMP assay.…”
Section: Discussionmentioning
confidence: 77%
“…Early studies of alphaherpesvirus recombination used strain virulence as a marker to detect recombinants (Wildy, 1955). Analysis of partial genome sequences were then used extensively to study recombination in several alphaherpesviruses, using tools such as PCR followed by restriction endonuclease cleavage fragment analysis of PCR products (PCR plus restriction fragment length polymorphism [PCR-RFLP]), gene deletion mutants, PCR hydrolysis probe assays and bioinformatic comparisons of partial genome sequences to detect recombination (Bowden et al, 2004;Christensen and Lomniczi, 1993;Dangler et al, 1993;Dohner et al, 1988;Glazenburg et al, 1994;Henderson et al, 1990;Javier et al, 1986;Kintner et al, 1995;Muylkens et al, 2009;Norberg et al, 2004;Sakaoka et al, 1995;Sakaoka et al, 1994;Schynts et al, 2003;Umene and Sakaoka, 1997). More recently, lower costs, improved technologies and greater access to next generation sequencing (NGS) techniques (Capobianchi et al, 2013;Pareek et al, 2011), statistical analysis (Bruen et al, 2006;Posada, 2002) and software to detect and estimate the likelihood of recombination (Huson and Bryant, 2006;Kosakovsky Pond et al, 2006;Kuhner, 2006;Lole et al, 1999;Martin et al, 2010;Martin et al, 2011;Martin et al, 2015;Pond and Frost, 2005;Wilson and McVean, 2006) have helped us to better understand recombination, and thereby provide insights into the role of recombination in the natural evolution of alphaherpesviruses (Burrel et al, 2015;Hughes and Rivailler, 2007;Kolb et al, 2013;Kolb et al, 2015;…”
Section: Introductionmentioning
confidence: 99%
“…The study of the relationships between these diseases and virus strains, and the analysis of transmission between individuals, requires accurate and reproducible typing and phylogenic analyses of clinical strains (4, 9). To achieve this, molecular technologies, in particular restriction fragment length polymorphism (RFLP) analysis, have been widely employed (12,13,14). However, the RFLP assay is relatively troublesome, and comparison of results obtained in different laboratories is difficult.…”
mentioning
confidence: 99%